Penerapan Aplikasi Mobile untuk Pembelajaran Angka dan Berhitung pada Anak Usia Dini - Maulana, Fazri; Efendi, Dwi Marisa; Prania, Dona (MDP Student Conference, 2025)
Learning numbers and counting is a fundamental foundation for the cognitive development of early childhood. However, conventional methods that are static and lack interactivity often make children easily bored and struggle to grasp concepts effectively. Therefore, innovation is needed in the form of an interactive mobile application that provides a more engaging, enjoyable, and flexible learning experience, allowing children to learn anytime and anywhere in a more effective way. This study employs a prototyping method, enabling iterative development with user feedback. The result of this research is a mobile-based learning application for early childhood education that presents number and counting materials in the form of text, images, and engaging animations. Additionally, it includes a quiz feature to assess children's understanding.